Attaining Satisfaction in Marriage: A Study of Marital Satisfaction Levels of Married Christians in a Developing Country - Adzovie, Rita Holm (Technium Social Sciences Journal, 2020)
Marriage is the foundation of all communities, societies and the nation at large. If marriages do not succeed, there is bound to be problems in society. Using the descriptive research design, this study sought to find out the levels of marital satisfaction of 400 married Christians in the Accra Metropolis, Ghana. The study found that Christian married men and women in Accra Metropolis were relatively satisfied in their marriages. Also, there were significant differences in marital satisfaction levels with regard to duration of marriage. Although there were no significant differences in marital satisfaction levels with regard to gender, females reported lesser satisfaction than males. Based on this, women were entreated to initiate counselling when needed to enhance their marital satisfaction.